Pelatihan Pembuatan Media Pmbelajaran Berbasis Canva AI dan Gamifikasi untuk Meningkatkan Kreativitas Guru SDN 1 Sumber Agung: Penelitian - Muhammad Nurwahidin; Riswandi; Roslina; Hesti Apala; Restiyanita; Akmal Nur; Anugerah Hisyam Safaat (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The training titled Developing Learning Media Using Canva AI and Gamification to Enhance Teacher Creativity at SDN 1 Sumber Agung was conducted to strengthen teachers’ ability to produce creative and interactive digital learning media that meet the needs of elementary school students. This study aims to describe the results of the training evaluation and analyze its impact on improving teacher creativity. A quantitative descriptive method was used, with data collected through a post-training evaluation questionnaire. The results show that teachers’ understanding of the material reached 89%, ease of technology use scored 86%, material relevance reached 92%, and overall satisfaction reached 90%. These findings indicate that the training was highly effective in enhancing teachers’ competencies, particularly in utilizing Canva AI and gamification elements to create engaging learning media. The results align with Mayer’s Cognitive Theory of Multimedia Learning, which emphasizes the importance of integrating visual and textual information to support cognitive processing. Overall, the training produced positive impacts, including increased creativity, improved digital literacy, and greater readiness among teachers to meet the demands of 21st-century learning.